Polymer Complexes for Electrocatalytic Oxygen Evolution - Shinohara, H.; Nishide, H. (KU Publ., 2022)
Electrocatalytic water oxidation for oxygen gas evolution has been widely studied from the perspective of sustainable technology. However, the use of organic polymers as catalyst layers for this reaction remains undeveloped. We discuss, here, the prerequisites, characteristics, and advantages of π-conjugated polymers as electrochemical catalysts to modify anodic current collectors for water oxidation, including some examples by citing the previous works in literature. In section 3, we present our latest results, the use of an organic polymer complex of poly(ethylenedioxythiophene) and phytic acid supported by a hydrophilic poly(hydroxyethyl methacrylate) platform, which efficiently generates oxygen gas through anodic water oxidation.
Оттегінің электрокаталитикалық бөлінуіне арналған полимерлік комплекстер
Полимерные комплексы для электрокаталитического выделения кислорода
Keywords: polymer complex; π-conjugated polymer; electrocatalyst; water oxidation; oxygen evolution; hydrophilic polymer; polythiophene; phytic acid